Hybrid position/force control of Stewart Manipulator using Extended Adaptive Fuzzy Sliding Mode Controller (E-AFSMC) - Navvabi, Hamed; Markazi, Amir H.D. (ISA transactions, 2019)
A new and effective control method is proposed for the hybrid position/force control of a Stewart Manipulator (SM). The control approach can be divided into the two parts, the first is an estimation of contact parameters between the robot and environment and the second one is the force control of manipulator according to estimated parameters. Hunt–Crossley nonlinear model is considered to describe the normal force in the contact region and Modified Extended Kalman Filter (MEKF) is used for estimating contact parameters. Extended Adaptive Fuzzy Sliding Mode Controller (E-AFSMC) is designed to hybrid position/force control of SM in the presence of state-dependent uncertainties. The proposed method is verified numerically, showing the effectiveness of the proposed method in critical situations such as actuator saturation, unexpected large disturbances, and state-dependent uncertainties. •This paper presents a new method for hybrid position/force control of Stewart Manipulator.•Extended Adaptive Fuzzy Sliding Mode Controller (E-AFSMC) has low dependency on the dynamic equations of the system.•The effectiveness of the proposed method has been verified using the software simulation in the loop.•The proposed method has very good performance under the challenging case of actuator saturation and unexpected uncertainties.